A multi-perspective and multi-method study on perceptions of English proficiency and pedagogical practices of NNESTs and NESTs in Chinese university classrooms - Jie Deng; Ke Li (LET: Linguistics, Literature and English Teaching Journal)
This study investigates the perceived English proficiency and teaching practices of non-native and native English-speaking teachers (NNESTs and NESTs) in Chinese universities, utilizing a multi-method approach including surveys, classroom observations, interviews, and focus groups. Data were collected from 118 students, four NNESTs, four NESTs, and two administrators to assess proficiency in English for general purposes (EGP) and English for teaching purposes (ETP). Qualitative and quantitative analyses indicate that NNESTs rate their ETP proficiency higher than their EGP, while NESTs perceive their EGP and ETP proficiencies to be superior to those of NNESTs. Administrators affirm NNESTs' ETP proficiency but raise concerns about NESTs' writing skills for ETP. Although a majority of students (n=65) showed no preference, focus groups suggest their preferences are context-dependent. The findings contribute to the understanding of ETP versus EGP proficiency and highlight the need for professional development in teaching competencies for both NESTs and NNESTs.